Processes and outcomes in student teamwork. An empirical study in a marketing subject - Bravo, Rafael; Lucia-Palacios, Laura; Martin, Maria J. (Studies in higher education (Dorchester-on-Thames), 2016)
The presence of student teamwork is increasing in most university degrees. However, there is still a gap in the literature regarding the connection between teamwork processes and their outcomes. In this paper, the authors analyze these processes and how they relate to teamwork outcomes from the students' perspective. Data was gathered from 129 undergraduates in the first year of an economics degree and analyzed by means of structural equations modeling. The main results show that transitional processes are especially important for explaining students' perceptions of goal attainment, whereas interpersonal processes are key to explaining perceptions of improvement in skills and overall attitude towards the team. Furthermore, this work shows that students' perception of goal attainment also exerts an influence on improvement in skills and on overall attitude towards the team. The relations found in this work may help instructors to develop effective teamwork activities and to monitor their results.